Neuroprotective Studies on Polygonum hydropiper L. Essential Oils Using Transgenic Animal Models - Tong, Xin; Li, Xiaoling; Ayaz, Muhammad; Ullah, Farhat; Sadiq, Abdul; Ovais, Muhammad; Shahid, Muhammad; Khayrullin, Mars; Hazrat, Ali (Frontiers in Pharmacology, 2021)
Polygonum hydropiper L. and related species are reported to possess neuroprotective potentials. In an attempt to validate its anti-Alzheimer's potentials, leaves oils (Ph.Lo) were extensively evaluated in this study against several in-vitro and in-vivo models of Alzheimer's disease. The Ph.Lo essential oils were analyzed via GCMS and tested against pathological targets of AD. The in-vitro and in-vivo assays were done for cholinesterase inhibition tests, anti-radical properties and cognitive assessments by using transgenic animal models. In preliminary cholinesterase inhibition assay, Ph.Lo essential oils was more active against AChE, BChE, DPPH, ABTS and H2O2 radicals and was evaluated for cognitive improvement using SWM, Y-Maze, Light and dark, open filed and balance beam tests. Animals Pre-genotyping was done via PCR to confirm APP transgene and brain homogenates of cortex and hippocampus for cholinesterase and free radicals’ studies. In SWM task, disease control animals treated with 10mg/kg of Ph.Lo for five days exhibited significant improvement in cognitive performance indicated by low escape times of 15.33 ± 4.39 sec on 5th day, compared with normal animals. In Y-Maze test, transgenic animals showed higher spontaneous alternation behavior (37.33 ± 4.17 %) as compared to disease control animals (26.33 ± 2.38%) and standard control group animals (40.83 ± 2.99) respectively. Ph.Lo therapy has improved the exploratory behavior (locomotion) and declined anxiety behavior in disease animals as accessed via open field test. Transgenic animals exhibited improvement in exploratory behavior (46.00 ± 5.19 lines crossed in 30 sec.) and spent 14.33 ± 0.88 and 11. 50 ± 0.86 in peripheral and central areas indicating less anxiety in comparison to diazepam treated group. Ph.Lo administration significantly augmented the motor and coordination abilities of transgenic animals when compared to other groups of animals and declined AChE, BChE activities as well as free radicals load in cortex and hippocampus tissues. Based on our finding, it is concluded that Ph.Lo exhibit significant neuroprotective potentials preliminary due to their anti-radicals and cholinesterase inhibitory activities. Ph.Lo need further detailed studies as potential aroma therapy against neurodegenerative disorders.